Passive Transparency Compensation for Bilateral Teleoperators with Communication Delays. (25th February 2015) - Rodríguez-Seda, Erick J.
Abstract : One of the main challenges in the realization of time-delayed bilateral teleoperators is the stable adaptation of transparency when the remote environmental dynamics are time-varying. In this paper, we propose a bilateral control strategy that passively adjusts the transparency of the system when the slave robot transitions between two different environments. The proposed controller exploits the effect that the wave impedance (a design parameter of the passivity-based scattering transformation) has on transparency without comprising closed-loop stability, regardless of time-varying communication delays. To properly adjust transparency, the control scheme smoothly switches the wave impedance parameter between a low value, ideal for free motion, and a sufficiently large value, suited for hard-contact tasks. We show that, by adopting this strategy, the transmitted impedance to the operator approximates more closely the environmental impedance value. Furthermore, we theoretically prove master-slave position coordination and force tracking under different scenarios. Simulation results illustrate the effectiveness of the proposed control strategy.